Analisis Penerapan Seven Tools Quality Control Pada Proses Produksi Bagian Sortation-Rejection Di PT. XYZ. - Febri Dwi Hariyani; Trio Yonathan Teja Kusuma (Universitas Muria Kudus, 2026)
This study aims to identify quality issues related to product rejection at PT. XYZ by applying the Seven Tools Quality Control approach to the sortation–rejection process. Rejection data for the July–August 2025 period were obtained through direct observation, interviews, and documentation. Pareto analysis shows that four major defect categories contributed the highest proportion of total rejection. In July, Honey Comb accounted for 18.82%, Fish Burn 18.76%, Powder Texture 18.44%, and Decompose 17.88%, resulting in a cumulative contribution of 73.90%. In August, Honey Comb increased to 26.79%, followed by Fish Burn at 21.32%, Powder Texture at 19.61%, and Decompose at 14.96%, with a total cumulative percentage of 82.68%. The p-chart indicates that the production process remained generally within statistical control limits, although several points exceeded these limits, indicating special-cause variations requiring further corrective actions. Fishbone analysis identifies raw material freshness, inconsistent processing methods, machine instability, and operator inaccuracy as the dominant factors contributing to Honey Comb and other defects. Overall, the application of the Seven Tools provides a clear quantitative representation of defect distribution and serves as an effective basis for establishing quality improvement priorities in the company.